4x+2+5x+3=3x+53

Simple and best practice solution for 4x+2+5x+3=3x+53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+2+5x+3=3x+53 equation:


Simplifying
4x + 2 + 5x + 3 = 3x + 53

Reorder the terms:
2 + 3 + 4x + 5x = 3x + 53

Combine like terms: 2 + 3 = 5
5 + 4x + 5x = 3x + 53

Combine like terms: 4x + 5x = 9x
5 + 9x = 3x + 53

Reorder the terms:
5 + 9x = 53 + 3x

Solving
5 + 9x = 53 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
5 + 9x + -3x = 53 + 3x + -3x

Combine like terms: 9x + -3x = 6x
5 + 6x = 53 + 3x + -3x

Combine like terms: 3x + -3x = 0
5 + 6x = 53 + 0
5 + 6x = 53

Add '-5' to each side of the equation.
5 + -5 + 6x = 53 + -5

Combine like terms: 5 + -5 = 0
0 + 6x = 53 + -5
6x = 53 + -5

Combine like terms: 53 + -5 = 48
6x = 48

Divide each side by '6'.
x = 8

Simplifying
x = 8

See similar equations:

| 5x+6y+9x= | | -330=10(-5x-3) | | 4x+8x+6x-24=x | | 5-(3-x)=6.5 | | M=682287/967540 | | -10(X-6)=6(10+2X) | | -4x+4(3x-13)=-140 | | 4x+8x+6x=24 | | -4(3-3m)=-37+7m | | 2(g-h)=b+y | | 9/7*-9/5 | | x^4-2x^3+14x^2-18x+45=0 | | 8k-k-5k+7-2k= | | -15+x+1=31 | | -4(2u-6)=-4-12u | | (6/5x)-(5/8)=(3/4x) | | -12-8(x-3)=-6(x-1) | | 6x-11x-12=-3(x-2) | | -(1+8X)=6-9X | | -9(10x+11)=351 | | 4-2y-y=2 | | tanx=(3/2)^(1/3) | | d=7+5x-8x | | 2x=1.8 | | 6-5x=9x-10x-6 | | 3x+7=8x-63 | | -12=-7–7/2s | | 14+7K=9K-2 | | -8(10x+3)=376 | | f(x)=4x^2-24x+31 | | 19v=-114 | | 3+4(x+6)=11 |

Equations solver categories